(untitled) (Progressive Agriculture, 2013)
The experiment was conducted in the Horticulture Farm of Sher-e-Bangla Agricultural University, Dhaka, Bangladesh during the period from October 2005 to December 2005 to study the effect of different levels of nitrogen and mulching on the growth and yield of Chinese cabbage. The tallest Chinese cabbage plant and spread of plant (43.12cm and 64.43cm) was recorded in 250kg N/ha and the shortest (36.15cm and 48.38cm) was recorded in 0 kg N/ha. The longest duration to start head formation (46.80 days) was recorded in 0 kg N/ha and the shortest (40.96 days) was recorded in 250 kg N/ha. The highest marketable yield per hectare of Chinese cabbage (120.06 ton) was recorded in 250 kg N/ha and the lowest yield (67.90 ton) was recorded in 0 kg N/ha. The highest Chinese cabbage plant, spread of plant (44.50cm, 58.28cm) during harvest period was recorded in black polythene mulch and the shortest plant and spread of plant (37.60cm and 49.58cm) was recorded in no mulch i.e. control. The highest days to start of head formation of Chinese cabbage (45.37) was recorded in no mulch and the lowest days (41.17) were recorded in black polythene mulch. The highest marketable yield per hectare of Chinese cabbage (123.27 ton) was recorded in black polythene mulch and the lowest yield (76.51 ton) was recorded in no mulch. In each and every case maximum growth and yield contributing characters and yield was observed in 250 kg N/ha and black polythene mulch and the reverse result was recorded in control condition i.e. no nitrogen and no mulch. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16845 Progress. Agric. 20(1 & 2): 27 33, 2009